Health seeking behavior of farming community in rural area of Titabor block in Jorhat district - Rahman, Syeda Jesmin; Das, Bishnu Ram; Nath, Gunjan (International Journal Of Community Medicine And Public Health, 2017)
Background: Numerous factors are associated with the access and utilization of health care services. These factors along with the preferences of the farmers are responsible for the health seeking behavior of farming community. This study aims to understand the health seeking behavior of the farmers and the factors influencing their behaviour in a rural block of Assam. Methods: A community based cross sectional study was done in a rural block of Jorhat district, Assam among a sample of 400 farmers. A pre designed pretested proforma was used to collect the data. Information was obtained on the demographic variables, health seeking behavior and the factors that may affect health seeking behavior. Results were analyzed using percentage and proportions. Results: The study revealed that respiratory tract infection (54.25%) was the most common cause of morbidity among farmers followed by musculoskeletal problems (23.25%) and gastrointestinal tract ailments (11.75%). Majority of the farmers preferred the government health facilities (62%) than the private practitioners (17%) for seeking treatment. Around 64% respondents sought health care only when their health conditions were severely affected. Financial constraints (43.25%) and lack of time (29.25%) was observed to be major impediment in utilization of health care services. Children were given most priority in seeking treatment at the time of illness (68.75%). Conclusions: Government health care facilities were preferred by most respondents due to low cost of services. Behavior seeking healthcare was mostly influenced by financial constraints.